New empirical insights into conflicting claims problems - José Manuel Giménez-Gómez; Maria del Carmen Marco Gil; Juan-Francisco Sánchez-García (SERIEs - Journal of the Spanish Economic Association, 2022)
The present paper aims to explore the perception of fairness in conflicting claims problems (O'Neill in Math Soc Sci 2(4):345-371, 1982). To do so, we present a questionnaire given to a large heterogeneous group of people (students, employees, retirees). Distributive justice criteria are studied through different ways of distributing scarce resources, and we analyse whether the population's response patterns are conditioned by specific features of the economic context. We find that proportional allocation is generally considered the fairest way of distributing resources. However, the principle of proportionality is abandoned by part of the population when claims represent needs and claimants have scarce resources. Moreover, we observe that age, employment status and education levels significantly influence the perception of fairness.
Keywords: D63; 330; Conflicting claims problems; Fair allocations; Social questionnaires